Clinopodium gracile Alleviates Metabolic Dysfunction-Associated Steatotic Liver Disease by Upregulating Peroxisome Proliferator-Activated Receptor α and Inhibiting Mitochondrial Oxidative Damage - Mingshi Ren; Jiayue Ren; Jianmei Zheng; Xiaotong Sha; Yining Lin; Feihua Wu (MDPI AG, 2024)
The most prevalent chronic liver disease, known as metabolic dysfunction-associated steatotic liver disease (MASLD), is characterized by an excessive accumulation of lipids and oxidative damage. Clinopodium gracile, a natural herbal medicine widely used by Chinese folk, has antioxidative, anti-inflammatory, and lipid metabolism-regulating effects. Here, we explored the effect of C. gracile extract (CGE) on MASLD using palmitic acid (PA)-induced hepatocytes and high-fat diet (HFD)-fed mice. In vitro, CGE could promote fatty acid oxidation and inhibit fatty acid synthesis and uptake to reduce lipid accumulation by regulating PPARα activation. Moreover, CGE could inhibit reactive oxygen species production and maintain mitochondrial homeostasis in PA-induced HepG2 cells. In vivo, animal study results indicated that CGE could effectively reduce lipid metabolism disorder, inhibit oxidative stress, and upregulate PPARα protein in the liver of HFD-fed mice. Molecular docking results also showed that active compounds isolated from CGE had low binding energy and highly stable binding with PPARα. In summary, these findings reveal that CGE may be a potential therapeutic candidate for MASLD and act by upregulating PPARα to reduce lipid accumulation and suppress mitochondrial oxidative damage.